Exploring the meaning of climate change discourses: an impression management exercise? - Nik Ahmad, Nik Nazli; Hossain, Dewan Mahboob (Emerald Group Publishing Ltd., 2019)
Purpose: This study aims to analyze how language is used to present climate change information in the narratives of Malaysian companies’ annual reports. Design/methodology/approach: The study uses content analysis and discourse analysis, and Brennan et al.’s (2009) impression management strategies and legitimacy theory were applied to explain findings. Findings: Much of the discourses are rhetorical in nature and can be considered as corporate attempts to appear concerned for climate change, consistent with an attempt to appear legitimate and manage impressions. Research limitations/implications: The first limitation is the purposive sampling used which limits the generalizability of the findings. The second limitation is that the study neglects to focus on companies in environmentally sensitive sectors which have more substantial adverse impacts. The third limitation is that the study did not examine all types of impression management strategies, limiting itself only to strategies which provide a favorable view of the firm. Finally, the study did not attempt to investigate the different levels of impression management strategies. Practical implications: A major practical implication is for regulators to consider mandatory climate change reporting at least for the sectors which contribute adversely to global warming. Originality/value: This is a first attempt to examine climate change discourses in a developing country. © 2019, Emerald Publishing Limited.